1998
DOI: 10.1017/s002211209800295x
|View full text |Cite
|
Sign up to set email alerts
|

Stability of plane Couette flow of a granular material

Abstract: This paper presents a linear stability analysis of plane Couette flow of a granular material using a kinetic-theory-based model for the rheology of the medium. The stability analysis, restricted to two-dimensional disturbances, is carried out for three illustrative sets of grain and wall properties which correspond to the walls being perfectly adiabatic, and sources and sinks of fluctuational energy. When the walls are not adiabatic and the Couette gap H is sufficiently large, the base state of steady fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
166
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(179 citation statements)
references
References 25 publications
12
166
1
Order By: Relevance
“…As one can see from Eq. (20), this happens, for a fixed f , when M becomes sufficiently small. Importantly, the final results (23) and (24) remain valid in the general case, as we obtained from the full, unreduced fourthorder dispersion equation for Γ(k).…”
Section: Linear Stability and Bifurcationsmentioning
confidence: 93%
See 2 more Smart Citations
“…As one can see from Eq. (20), this happens, for a fixed f , when M becomes sufficiently small. Importantly, the final results (23) and (24) remain valid in the general case, as we obtained from the full, unreduced fourthorder dispersion equation for Γ(k).…”
Section: Linear Stability and Bifurcationsmentioning
confidence: 93%
“…One can obtain this solution directly by putting λ = 0 in Eq. (20). Therefore, the assumption of a nonzero λ [the specific form of viscosity divergence, Eq.…”
Section: Steady Shear Flow Close To Crystallizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Another well-known source of instability in granular flows is inelasticity. Studies on two-dimensional shear flows have shown that the dissipation due to inelastic collisions can lead to the formation of clusters (Savage 1992;Chi-Hwa Wang et al 1997;Alam & Nott 1998;Nott et al 1999). In order to better understand the role of dissipation in our problem, we have performed the stability analysis by setting to zero the collisional rate of energy dissipation γ in the linearized energy equation.…”
Section: Instability Mechanism and Role Of The Inelasticitymentioning
confidence: 99%
“…When a shear is applied to the granular system, high-density region, called "shear band", appears [7]. There exist many papers to estimate the transport coefficients by using kinetic theory [8,9,10,11,12,13] and to analyze the pattern dynamics by using continuum mechanics [14,15,16,17,18,19,20,21,22].…”
Section: Introductionmentioning
confidence: 99%